What I didn’t grow up with is dangerous: personal experience with a new technology or societal change reduces the belief that it corrupts youth - Protzko, John; Schooler, Jonathan W. (Frontiers in Psychology, 2023)
Throughout history, new technological/societal changes have been viewed with suspicion, their influences interpreted as damaging, corrupting, and a potential cause of societal downfall. The youth of the day are particularly seen as the victims of such developments. Why do we keep seeing technology/societal change as harmful to young people? Two studies (N = 1,702 combined) examine what technological/social factors people believe contribute to the corruption of the youth. In a pilot study, American adults generated a list of technological/societal innovations that they viewed as particularly problematic for youth in assorted ways. In study 2, we mapped the belief that specific technological/societal changes are corruptive onto whether American adults experienced them while growing up. Here we show that people see technologies that are more modern as particularly corrupting of today’s youth. We further show a robust within-person relationship between people’s exposure to particular technologies in childhood and their belief that the experienced change is corrupting the youth of ‘the present’. People are more likely to see technological/societal changes as corrupting if they did not experience it themselves growing up (b = -.09, p < .001, 95%CI = [-.11, -.09]). Intriguingly, however, reminding people of their own exposure to a particular innovation growing up reduces their perception of its potential harm. Thus, as society continues to progress with new innovations, we may continue to ‘see’ technological/societal changes we did not grow up with as corrupting the youth of the future—in a vicious cycle that may persist indefinitely or at least until its likely source (mere unfamiliarity) is more widely recognized.